Are people with opioid dependence who inject opioids different from those who do not? – Findings from a cross-sectional, observational, community-based study from North India - Pooja Shakya; Ravindra Rao; Alok Agrawal; Roshan Bhad; Atul Ambekar; Deepak Yadav (Indian Journal of Social Psychiatry, 2024)
Background: About one-fourth of individuals who are dependent on opioids use opioids through injecting route. Most of such individuals start using opioids through noninjecting route much earlier before they transition to injecting opioids. It is important to identify important factors that delineate individuals who inject opioids from those who use opioids through other routes, which was the objective of the present study. Methods: This was a cross-sectional study design. Four hundred treatment-naïve opioid users with opioid dependence were selected using a snowballing sampling technique. The drug use details, family relations, social and occupational functioning, and peer network history were assessed using a self-developed questionnaire and the use of structured instruments such as the Leeds Dependence Questionnaire Scale, High-Risk Behavior Scale, and Functional Status Questionnaire Scale. Comorbid psychiatric symptoms were assessed using the Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9. The Ask Suicide-Screening Questions was used for assessing different domains of suicidality. Results: The mean age of the participants was 26 (standard deviation = 6) years. One-third (n = 136) of these were injecting opioid users (injecting drug users [IDUs]) and the remaining were taking opioids through other routes (non-IDUs). In multivariate analysis, IDUs (as compared to non-IDUs) had higher rates of family history of opioid use (odds ratio [OR] =3.53, 95% confidence interval: 1.17–8.69), incarceration history (OR = 2.16, 1.78–3.11), lower employment (OR = 0.53, 0.31–0.84), more people with <5 years of education (OR = 4.31, 2.60–12.73), lower age of starting opioid use (OR = 0.44, 0.26–0.69), more concurrent sedative use (OR = 5.60, 4.34–7), more self-harm attempts history (OR = 1.88, 1.16–3.2), larger peer groups (OR = 1.89, 1.11–2.63), and greater involvement in selling illegal drugs (OR = 1.81, 1.49–3.67). Conclusions: Various factors are significantly associated with using opioids through injecting route in individuals with opioid dependence. These factors can help identify individuals with opioid dependence who are likely to transition to injecting opioids.